The role of government : a business entities' comparision between Europe and Southeast Asia - Volasay Chittachone (2008)
In this study we compare the relationship between the state and business in Europe and Southeast Asia in what can be labeled a mixed economy paradigm. Our study found that with the exception of the welfare component, Southeast Asians adopted the European model virtually in toto, which they believed better enabled the state to play an active role in the allocation of national resources for development. We argue that the relationship between business and the state is better understood against the political-economic background of each region and country. The determinants of the role that government plays in the ownership and management of business entities are rooted in the social, economic, and consequently, political circumstances that exist at a given point in time. As a result, although both Southeast Asians and Europeans subscribed to the capitalist mode of production, there are subtle, but nonetheless significant differences among all the countries studied in terms of the role of government in business.